KEPATUHAN BIDAN DESA TERHADAP STANDAR OPERASIONAL 7T PADA PELAYANAN ANTENATAL DI KABUPATEN SEMARANG TAHUN 2011 - Rahayu, Sri; Kartasurya, Martha Irene; Sriatmi, Ayun (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2012)
Coverage of K4 in Semarang district in 2009 had not reached the target (90.1%). Preliminary study indicated that the average village midwives compliance to the implementation of antenatal service based on the standard of 7T was only 70%. The objective of this study was to know psychological and organizational factors that influenced midwives compliance to the operational standard of 7T in antenatal services in Semarang district.This was an observational study with analytical characteristic and using cross sectional approach. Data were collected by doing observation and interview using structured questionnaire. Dependent variable in this study was midwives compliance and independent variables were attitude, motivation, supervision, leadership, communication and facilities. The study subjects were 71 village midwives that were selected randomly and proportionally. Bivariate analysis was done using Rank Spearman test and multivariate analysis was done by applying logistic regression. Results of the study showed that most of respondents were between 25 and 46 years old with average of working period of 13.3 years. The average of village midwives compliance was 76%. Psychological factors, attitude and motivation of respondents, were mostly good. Organizational factors: perception towards supervision of coordinator midwives, perception on the head of puskesmas leaderships, perception on the midwives coordinator communication and facilities, were all good.Results of correlation test showed that attitudes, motivation, leaderships, communication and facilities variables were associated with compliance to the operational standard of 7T. On the other hand, perception on supervision was not related to the operational standard of 7T. Result of logistic regression test indicated that motivation, facilities and communication perception variables jointly influenced village midwives compliance.Village midwives compliance to the operational standard of 7T, especially hemoglobin and protein in the urine examinations, needed to be improved. Motivation of village midwives needed to be increased by conducting refreshing related to antenatal services. Sanction for midwives who did not comply the standard of 7T had to be applied. The number of facilities especially hemoglobin, protein in the urine examination tools and counseling media, had to be added gradually. Key words : Operational standard of 7T, antenatal services, village midwives, compliance